The influence of nickel intermetallic coatings content on wear mechanisms in term of high-temperature friction - Уманский, А.П.; Полярус, Е.Н.; Костенко, А.Д.; Терентьев, А.Е. (Problems of Tribology, 2014)
The influence of plasma-deposited coatings content on their wear resistance during high-temperature friction tests has been investigated. The influence of test temperature on the coatings tribological performances has been studied. The some differences of the mechanisms of wear due to the formation of oxide films of various compositions on the friction surfaces have been established.